Hydrogen bonds between methanol and the light liquid olefins 1-pentene and 1-hexene: From novel application to fundamental science - Zhang, Z; Xiao, T; Al-Megren, H; Aldrees, S; Al-Kinany, M; Kuznetsov, V; Kuznetsov, M; Edwards, P (Royal Society of Chemistry, 2017)
We have recently developed a new extraction process for significantly reducing the olefin content in commercial FCC gasoline. To gain insights into the origins of this process , we have investigated the dissolution of the light liquid olefins 1-pentene and 1-hexene in methanol through computer modelling together with NMR spectroscopy. We find two important hydrogen bonding modes for methanol olefin interactions – namely, O-H···π and C-H···O.